Distribution and Abundance of Violin Crabs (Uca sp.) In The Mangrove Ecosystem Area of Tarakan City and The Potential of Implementation In Biology Learning - Wahid, Abdul; Nursia, Nursia; Adhani, Aidil; Rupa, Darius (Biopedagogia, 2024)
The mangrove ecosystem area of Tarakan City has a wide variety of flora and fauna where the dominant group is invertebrate fauna such as snails and crabs, one type of crab in the mangrove ecosystem is the Violin Crab (Uca sp). This type  of  research  is  an  exploratory  descriptive  study  with  a  quantitative  and qualitative. Based on the results of the distribution analysis of the Violin Crab (Uca sp) the distribution percentage value was categorized as group except for Uca vocans which was categorized as normal. Station II, the residential area of Lingkas Ujung, Uca demani, Uca tetragonon, Uca chlorophthalmus crassipes, the percentage distribution is categorized in groups. For the results of the abundance of violin crabs (Uca sp) which has a relatively high relative abundance of species at station I, Uca demani 69.41% is categorized as the highest and Uca vocans 0% is categorized as the lowest and lowest. Station II in the Lingkas Ujung Uca residential area with 79.58% categorized as the highest and Uca chlorophthalmus crassipes 9.54% categorized as the lowest. Finally, for the results of the analysis of the relationship between research and Biology learning regarding violin crab research related to the syllabus for high school biology subjects, namely basic competencies 3.2 Analyzing various levels of biodiversity in Indonesia and their threats and conservation and 4.2 Presenting the results of observations of various levels of biodiversity in Indonesia.